TINGKAT PENGETAHUAN DAN KEPATUHAN TERHADAP KUALITAS HIDUP PASIEN TUBERKULOSIS DI PUSKESMAS CIKARANG - Damayanti, Nanda; Dewi, Masita Sari; Adiwisastra, Nuzul Gyanata; Rosiana, Rosiana (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Tuberculosis (TB) remains a major public health problem in Indonesia, including Bekasi Regency, which has a high disease burden. A decline in quality of life is commonly experienced by TB patients due to clinical symptoms, social stigma, and adverse drug effects. Although patient knowledge and treatment adherence are widely believed to influence therapeutic outcomes, evidence regarding their impact on quality of life remains inconsistent and limited, particularly in the Cikarang region. This study aimed to examine the relationship between knowledge level and treatment adherence with the quality of life of pulmonary tuberculosis patients at Puskesmas Cikarang Utara. A cross-sectional design was employed involving 93 outpatient pulmonary TB patients who met the inclusion criteria, including age 17–65 years, undergoing category I/II therapy, able to communicate, and willing to participate, as well as exclusion criteria of having significant comorbid conditions. Participants were selected using purposive sampling. Data were collected using a structured knowledge questionnaire, the Morisky Medication Adherence Scale (MMAS-8), and the Short Form-36 (SF-36). Statistical analysis was performed using the Chi-Square test. The majority of respondents demonstrated good knowledge (86%), moderate to high treatment adherence (86%), and a high quality of life (55.9%). Chi-Square analysis indicated no significant association between knowledge level and quality of life (p = 0.468), nor between treatment adherence and quality of life (p = 0.962). These findings suggest that knowledge and adherence alone are insufficient determinants of quality of life among pulmonary TB patients. Therefore, improving patients’ quality of life requires comprehensive interventions. Beyond treatment adherence.